ANALISIS PENGARUH PERSEPSI PASIEN ATAS KUALITAS JASA RAWAT INAP TERHADAP KEPUASAN PASIEN DI RUMAH SAKIT RSI DURUS SYIFA' MUSLIMAT NU BENOWO SURABAYA - Julindrastuti, Dijah (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2005)
The aim of study is to analyze the impact of patiant perceptiont of service quality to patiant satisfaction Darus Syafi 'Muslimah NU at Benowo Surabaya. When analyze on opinion of 100 samples from population with accidental sampling technique and questionairre as tools for collecting the data. this study shows that there are significance impacts.